Does Stress-Related Growth Really Matter for Adolescents' Day-to-Day Adaptive Functioning?. (May 2017) - Mansfield, Cade D.; Diamond, Lisa M.
Adolescent stress-related growth refers to enhancement in an adolescent's cognitive-affective or social resources as a result of experiencing stressors. We tested whether adolescents reporting high levels of stress-related growth showed superior adaptation outcomes on a day-to-day basis. Participants ( n = 91; females = 46, age = 14) completed a questionnaire measure of stress-related growth and kept a diary of emotional and interpersonal functioning for 10 consecutive days. Individual differences in cognitive-affective stress-related growth moderated associations between daily stress levels and adaptive coping behaviors, whereas individual differences in social stress-related growth moderated associations between daily mother-child conflict and end-of-day negative affect. This study provides the first empirical demonstration of domain-specific forms of stress-related growth during adolescence.